2002
DOI: 10.1016/s0009-2614(02)00774-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic polarization at surfaces and thin films of organic molecular crystals: PTCDA

Abstract: The electronic polarization energies, P = P+ + P−, of a PTCDA (perylenetetracarboxylic acid dianhydride) cation and anion in a crystalline thin film on a metallic substrate are computed and compared with measurements of the PTCDA transport gap on gold and silver. Both experiments and theory show that P is 500 meV larger in a PTCDA monolayer than in 50Å films. Electronic polarization in systems with surfaces and interfaces are obtained self-consistently in terms of charge redistribution within molecules. I. TRA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
167
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(195 citation statements)
references
References 15 publications
23
167
1
4
Order By: Relevance
“…4 may also explain the negative outcome of the attempts to measure surface core-level shifts for thin films of organic semiconductors [12,13]: If the crystal structure of the films is such that the polarization screening of the photohole is mainly effected by molecules located in a plane parallel to the surface, surface core-level shifts are expected to be very small. In this sense, the present data reconcile the conflicting evidence with respect to polarization screening in Refs [11][12][13].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…4 may also explain the negative outcome of the attempts to measure surface core-level shifts for thin films of organic semiconductors [12,13]: If the crystal structure of the films is such that the polarization screening of the photohole is mainly effected by molecules located in a plane parallel to the surface, surface core-level shifts are expected to be very small. In this sense, the present data reconcile the conflicting evidence with respect to polarization screening in Refs [11][12][13].…”
supporting
confidence: 87%
“…For example, it has been shown that the chemical bonding to a metal surface may change both the electronic levels and geometric structure of organic semiconductor molecules profoundly [5][6][7][8][9]. During charge transport, the electronic states of a molecular material may also be influenced by polarization screening, i.e., the stabilization of a locally injected charge through the polarization of the surrounding molecular environment [10,11]. While the principles of polaron-formation are well understood, the new aspect which we report here, namely, the site specificity of the polarization energy in complex unit cells and at surfaces of organic materials, was not experimentally proven so far.…”
mentioning
confidence: 99%
“…[19]) and a CNL located 3.5 eV above the center of the HOMO level, E HOMO . We find that, upon adsorption, image potential effects [29] strongly reduce the energy gap to around 1.9 eV, and E CNL -E HOMO to 1.0 eV. These effects are calculated using a classical image potential with a metal image plane located 1.25 Å [30] from the outermost Cu layer.…”
Section: Prl 100 027601 (2008) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 95%
“…Due to image potential contributions at the metal-organic contact in the nanometer range a reduction of the barrier height is expected. [31][32][33][34]1 We observe the resulting opening of the transport band gap within the first 4 nm film thickness by a value of 0.15 eV to 0.20 eV for both HOMO and LUMO regions. At the MnPc/Co interface a constant interface dipole = (−0.7 ± 0.1) eV is observed indicating charge transfer between the MnPc molecules and the metallic substrate, as already observed in the case of MnPc/Au.…”
mentioning
confidence: 99%